2017
DOI: 10.12973/eu-jer.6.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Interactive Story Reading Method on Receptive and Expressive Language Vocabulary of Children

Abstract: This study aims to review the impact of the interactive story reading method on 48-72 month children's vocabulary based on receptive and expressive language. The study group is 52 children in the 48-72 months age group at the nurseries of primary schools at Ankara province. The research employed a combined pattern analyzing both quantitative and qualitative data. The data were collected via "General Information Form" ,"Expressive and Receptive Language Test in Turkish (TIFALDI)" developed under the leadership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
8
0
2
Order By: Relevance
“…IBR was found to have a significant impact on participants’ general vocabulary in studies of both small group (Simsek & Erdogan, 2015; d = 1.12 c ) and whole-class delivery (Okyay & Kandir, 2017; d = 0.62 c ). However, the results from Ergül et al (2016) were less consistent as whole-class delivery led to statistically significant differences in participants’ general vocabulary on just one of two standardised vocabulary measures employed ( d = 0.8 c ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…IBR was found to have a significant impact on participants’ general vocabulary in studies of both small group (Simsek & Erdogan, 2015; d = 1.12 c ) and whole-class delivery (Okyay & Kandir, 2017; d = 0.62 c ). However, the results from Ergül et al (2016) were less consistent as whole-class delivery led to statistically significant differences in participants’ general vocabulary on just one of two standardised vocabulary measures employed ( d = 0.8 c ).…”
Section: Resultsmentioning
confidence: 93%
“…The most commonly evaluated strategy was IBR, generally with positive outcomes. Even after short periods of intervention (studies ranged from 8 days to 8 weeks), and across different modes of delivery, studies reported significant positive effects on general (Okyay & Kandir, 2017, d = 0.62 c ; Simsek & Erdogan, 2015, d = 1.12 c , respectively) and specifically targeted vocabulary (Lever & Sénéchal, 2011, d = 0.66; Opel et al, 2009, d = 0.66). However, these were small-scale studies and the mixed findings in Ergül et al (2016) (which were in part attributed to teacher aptitude) highlight the need for larger scale, randomised studies if more robust conclusions are to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Daha önce yapılan araştırmalar etkileşimli kitap okuma yönteminin çocukların dil gelişimini (Okyay ve Kandır, 2017;Peter, 2017;Saracho, 2018), bilişsel becerilerini (Dowdall vd., 2017;Er, 2016) ve sosyal-duygusal becerilerini (Fettig vd., 2018) desteklediğini göstermektedir. En fazla gelişim görülen 'problem durumu' ve 'olay örgüsü' kategorileri için, çocukların daha fazla çeşitlilik içeren ve daha fazla sayıda olayı anlatma becerisi, doğrudan, kelime dağarcığı ve ifade edici dil gelişimiyle (Kang, Kim ve Pan, 2009) ve çeşitli temalar etrafında organize edilmiş nedensel, yapılandırılmış ve mantıksal bağlantılara sahip bir olay örgüsü oluşturabilmeleri ise bilişsel gelişimleriyle ilişkilidir (Reilly vd., 2003).…”
Section: Discussionunclassified
“…Shared SR experiences are also linked to language development (Mol & Buss, 2011), i.e. receptive (Meng, 2015;Sénéchal & Lefevre, 2002) and expressive language (Okyay & Kandir, 2017;Saracho, 2017;Sénéchal et al, 1998), improved oral and spoken narrative skills (Dockrell, Stuart & King, 2010), and improved listening and communication skills (Golloher, 2015) Awareness that book language differs from daily conversation develops when children listen to stories and is evident when children begin to pro-duce literary language, such as "One day he said ..." or when they talk like a book (Clay, 1979). They realise that the vocabulary, and the syntax and intonation patterns of book language differ from everyday speech.…”
Section: Literature Review Storybook Reading As An Emergent Phenomenonmentioning
confidence: 99%